2018
DOI: 10.1002/pc.24979
|View full text |Cite
|
Sign up to set email alerts
|

The Using of Graphene Nano‐Platelets for a Better through‐Plane Thermal Conductivity for Polypropylene

Abstract: In‐plane alignment of graphene nanoplatelets (GNPs) in thin thermal interface material layers suppresses the through‐plane heat transport, which limits the performance of materials. In order to suppress the in‐plane alignment of the GNP filler within polypropylene (PP) and increase the through‐plane component, modification of GNP (MG) was performed in this study. For this aim, GNP was treated with diallyldimethylammonium chloride solution and filled with PP at different weight fractions by using a laboratory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…As a result of these networks, enhanced thermal conductivities (3.788, 5.807, 5.922, and 8.094 W/m•K for M5 30 wt.%, M15 30 wt.%, and M25 20 and 30 wt.%, respectively) were observed, with increases of 657.6%, 1061.4%, 1084.4%, and 1518.8% compared to the neat pCBT. Table S1 summarizes the in-plane thermal conductivities of composites with GNP fillers reported in previous studies [13,22,[25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…As a result of these networks, enhanced thermal conductivities (3.788, 5.807, 5.922, and 8.094 W/m•K for M5 30 wt.%, M15 30 wt.%, and M25 20 and 30 wt.%, respectively) were observed, with increases of 657.6%, 1061.4%, 1084.4%, and 1518.8% compared to the neat pCBT. Table S1 summarizes the in-plane thermal conductivities of composites with GNP fillers reported in previous studies [13,22,[25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…Seki et al showed that through plane conductivity of 20 wt% graphene filled PP is better than 20 wt% SG filled PP composite. However in terms of in‐plane thermal conductivity, 20 wt% SG filled PP composite has a larger conductivity value than that of 20 wt% graphene filled PP composites . In the study of King et al, 30, 40, 50 wt% of SG were loaded into PP and in‐plane thermal conductivity of the composites based on guarded heat flow meter method values were measured to be 1.387, 2.573, and 4.373 W/mK, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…A value called specific thermal conductivity enhancement (specific TCE) was estimated by eq , for comparison of our results with polyolefin composites reinforced with different types of nanofiller structure along the preferred direction of heat transfer. where κ c and κ m are the thermal conductivity of the composite and the matrix (W m –1 K –1 ), respectively, and wt % is the filler content (κ c ≈ 9.26, κ m ≈ 0.41, and ∼2.98 wt % filler loading in case of M- o -GWF/PE). The summary in Figure g and Table S7 indicates that our M- o -GWF/PE composites exhibit a high specific TCE of ∼719 along the preferred direction, which is a record-high value compared to existing nanofiller/polyolefin composites in the literature. ,, A finite element simulation was performed using ANSYS fluent software to elucidate the benefits of our samples compared to the other three types of polyolefin composites, and the details can be found in the Supporting Information (Figures S17 and S18 and Table S8). The simulation includes three typical models of nanofillers in the polyolefin matrix except our case, as shown in Figure h: type I, randomly distributed nanofillers in the matrix prepared by melt blending; type II, partial alignment induced by cyclic stretch; type III, interconnected networks constructed by the connection of nanofillers, such as using the encapsulation method. ,,, As a result, in Figure i and Figure S19, M- o -GWF/PE composites have a higher upper temperature with a uniform temperature distribution among the four models at the same simulation time, demonstrating the superior heat transfer capability of our samples due to the formation of a high-quality, well-aligned, and seamless graphene framework in the matrix.…”
Section: Results and Discussionmentioning
confidence: 96%